PARTISIPASI PENYUSUNAN ANGGARAN DAN KOMITMEN ORGANISASI DENGAN KINERJA ORGANISASI - Novandalina, Arini (JURNAL STIE SEMARANG, 2017)
ABSTRACT This research test influence mediation organization culture in relationship participation of composing a budget and organization commitment with organization performance.Samples of this research is teachers SMA City in Semarang, with a quota sampling.A method of analysis used to test a questionnaire is reliabilitas and validity test. While technique regression analysis using mediation, by fit model appropriateness and test assumption classic. The result showed that only participation of composing a budget and commitment of the organization that influential positive significantly affect the organizations cultural, and organization cultural significant positive influence on the performance of the organization.While the participation of composing a budget and commitment of the organization no significant positive on the performance of the organization.But organization cultural it is proven as variable mediation relations participation of composing a budget and commitment of the organization with the performance of the organization.   Keywords : Participation in the preparation of the budget, organizational commitment, organizational culture and organizational performance.   ABSTRAK Penelitian ini menguji pengaruh budaya organisasi mediasi dalam hubungan partisipasi penyusunan anggaran dan komitmen organisasi terhadap kinerja organisasi. Sampel penelitian ini adalah guru SMA Kota Semarang, dengan kuota sampling. Metode analisis yang digunakan untuk menguji kuesioner adalah reliabilitas dan validitas. uji. Sedangkan teknik analisis regresi menggunakan mediasi, dengan kesesuaian model pas dan uji asumsi klasik. Hasil penelitian menunjukkan bahwa hanya partisipasi menyusun anggaran dan komitmen organisasi yang berpengaruh positif berpengaruh signifikan terhadap organisasi budaya, dan pengaruh signifikan budaya organisasi terhadap kinerja organisasi. Sedangkan partisipasi menyusun anggaran dan komitmen organisasi tidak ada. signifikan positif terhadap kinerja organisasi. Namun budaya organisasi terbukti sebagai variabel hubungan mediasi partisipasi menyusun anggaran dan komitmen organisasi dengan kinerja organisasi.   Kata kunci:    Partisipasi dalam penyusunan anggaran, komitmen organisasi, budaya organisasi dan kinerja